Constituição do território a partir do movimento de trabalhadores do bairro Jardim das Américas Guarapuava/PR - Lima, Leandro de Almeida (2013)
This dissertation is result of research done during 2007 2013. This led to studies about social movements of workers occurred in the Jardim das Américas, district of municipality Guarapuava PR. The reality of the city and the neighborhood is related in many aspects to the global problem of inequality, as this is signed in a model of production and consumption founded on the exploration of human beings and nature, subjecting a large population to poor conditions, and the inequalities are fundamental to the existence of capitalism. Whit the changes in production mode and work organization, in the field and in the city, many peasants and rural workers migrate to the cities searching employment, as not sufficient to meet the demand of migrants, subjecting workers to underemployment. The analysis categories selected were territory and social movements, they are essential to analyze the space organization. Studying social movements with a geographical look is necessary to advance in understanding of space construction and territorialization of different groups. Forward to the precarious living conditions of working class, social movements constitute an important role in reducing inequalities and injustices, because they propose a different way of society organization and a way of ordering the space that questions the structures of domination, breeding inequality social. Thereby, the group exerts power over space, in decision making on reordering, territorializing it through the actions of movements. Accordingly, the goal of this research was undestand the main aspects that influence the production of the territory by the workers in the Jardim das Américas neighborhood. Specifically it was necessary to examine how social movements assist in the establishment of the territory, find out how the build collective knowledge enabled territorial changes; to investigate how rural exodus step in the socioeconomic conditions of the studies area; to identify and characterize the subjects involved in the process; and develop a study about the changes in the construction of the territory until this date. The research method used was action-research, which is basically the investigate act in strait relationship with the acting, with the subjects that are part of the theme studied and also were made fieldwork observations, dialogue and attendance the group s activities, as well interviews and questionnaires